Phylogenetic analysis and redefinition of the maculata species group of Epicauta (Meloidae: Meloinae: Epicautini) - Campos Soldini, Maria Paula (2015)
A cladistic analysis based on 81 morphological characters was performed in order to determine the phylogenetic relationships of 11 species of Epicauta from South America. We find that the 11 South American species constitute a monophyletic group together with all the North American species of the Epicauta maculata group. Within this clade, the 11 species from South America conforms an apical monophyletic group within the E. maculata group. We propose to maintain the validity of the Epicauta maculata group, but also to redefine it with new characters. The South American species of the Epicauta maculata group are also described and illustrated. We propose the following nomenclatural changes: Epicauta rosilloi Martínez, junior synonym of Epicauta minutepunctata Borchmann; Epicauta fourcadei Denier, junior synonym of Epicauta fulvicornis (Burmeister), and Epicauta breyeri Denier, junior synonym of Epicauta nigropunctata Blanchard. We provide an identification key, new host plant associations, and updated geographic distribution.